Pengaruh Product Knowledge dan Perceived Value terhadap Keputusan Pembelian Sepeda Motor Kawasaki Klx 150cc pada PT. Duta Intika Denpasar - Astawa, I Putu; Wijaya, Putu Yudy; Astawa, I Putu Putra (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study is to determine the influence of product knowledge and perceived value on the purchase decision of the Kawasaki KLX 150CC motorcycle at PT. Intika Denpasar Ambassador. The number of samples in this study was 130 respondents using the accidental sampling method. The data analysis technique used in this study is a research instrument test which is then continued with multiple linear regression analysis, determination coefficient test, T test and F test. Duta Intika Denpasar with a t-count value of 4,160 > t-table of 1,978 and a significant value of 0.000 < 0.05. 2) There is a positive and significant influence between perceived value on purchasing decisions in PT. Duta Intika Denpasar with a t-count value of 6.448 > t-table of 1.978 and a significant value of 0.000 < 0.05. 3) Product knowledge and perceived value simultaneously have a positive and significant effect on purchasing decisions at PT. Duta Intika Denpasar with a F-count value of 31,815 > an F-table of 3.07 and a significant value of 0.000 < 0.05. The advice given to PT. Duta Intika Denpasar should maintain the quality of the motorcycle so that it is in prime condition when purchased by consumers, explaining the benefits and advantages of motorcycles in order to improve consumers' decisions to buy motorcycles